Penguatan Pendidikan Agama Islam Dalam Kehidupan Sehari-Hari Melalui Literasi Digital Untuk Membentuk Karakter Generasi Z - Mario Darusman; Sucahyo Oktafian Mugihono; Nila Oktavia Dwiningrum; Imam Prihardiyanto; Benny Prasetiya (Education Research Center, 2026)
The rapid advancement of digital technology has significantly transformed the way Generation Z learns, communicates, and interacts in daily life. As digital natives, Generation Z faces both opportunities and challenges, particularly in accessing religious information through digital media. This study aims to analyze the strengthening of Islamic Religious Education (IRE) in everyday life through digital literacy as an effort to develop the character of Generation Z. This research employed a qualitative approach using a library research method by examining relevant scientific literature, books, and journal articles related to Islamic Religious Education, digital literacy, and character education. Data were collected through documentation techniques and analyzed using content analysis. The findings indicate that the integration of digital literacy into Islamic Religious Education enhances students' ability to access, evaluate, and utilize digital information critically based on Islamic values. Furthermore, digital literacy contributes to the development of religious values, honesty, discipline, responsibility, tolerance, and ethical behavior in digital environments. The successful implementation of strengthening Islamic Religious Education through digital literacy requires collaboration among families, schools, communities, and the government to establish an educational ecosystem that is adaptive to technological developments while maintaining Islamic values. Therefore, digital literacy serves as an effective strategy for strengthening character education among Generation Z in the digital era